PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG DI KELAS VI MI PERSIS GANDOK KOTA TASIKMALAYA - Rohman, Taufik; Risa Nuri Sahar (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aimed to examine the use of audio-visual media on mathematics learning outcomes in spatial construction material in class VI MI Persis Gandok, Tasikmalaya City. This research is a pre-experimental design type One group Pretest – Posttest design research. The research was carried out at MI Perisis Gandok, Tasikmalaya City, academic year 2023/2024. The population of this research is all MI students in West Java, while the target population is MI Persis Gandok students, in Tasikmalaya City. The sample in this study used a purposive sampling technique. From the affordable population, one class was selected as the research sample, namely class VI-B. The research instrument was a description test which had previously been analyzed by two mathematicians. Analysis of the research results was carried out using SPSS Ver.25 software. Data processing for testing the influence of the use of audio-visual media on mathematics learning outcomes in spatial building material was carried out using the t-test at a significance level of 5% (ά=0.05). The research results showed that the average pre-test score was 73.58 the post-test score was 85.65 and the Sig. (2-tailed) of 0.000 then Ha is accepted (H0 is rejected). This means that there is an influence of the use of audio-visual media on Mathematics learning outcomes in spatial construction material in Class VI MI Persis Gandok, Tasikmalaya City.